NK Cell Subgroups, Phenotype, and Functions After Autologous Stem Cell Transplantation - Jacobs, Benedikt; Tognarelli, Sara; Poller, Kerstin; Bader, Peter; Mackensen, Andreas; Ullrich, Evelyn (Frontiers in Immunology, 2015)
High-dose chemotherapy with consecutive autologous stem cell transplantation (autoSCT) is a well-established treatment option for patients suffering from malignant lymphoma or multiple myeloma. Natural killer (NK) cells are an important part of the immune surveillance, and their cell number after autoSCT is predictive for progression-free and overall survival. To improve knowledge about the role of NK cells after autoSCT, we investigated different NK cell subgroups, their phenotypes and their functions in patients treated with autoSCT. Directly after leukocyte regeneration (>1000 leukocytes/μl) following autoSCT, CD56++ NK cells were the major NK cell subset. Surprisingly, these cells showed unusually high surface expression levels of CD57 and KIR compared to expression levels before or at later time points after autoSCT. Moreover, these NK cells strongly up-regulated KIR2DL2/3 and KIR3DL1, whereas KIR2DL1 remained constant, indicating that this cell population arose from more immature NK cells instead of from activated mature ones. Remarkably, NK cells were already able to degranulate and produce IFN-γ and MIP-1β upon tumor interaction early after leukocyte regeneration. In conclusion, we describe an unusual up-regulation of CD57 and KIRs on CD56++ NK cells shortly after autoSCT. Importantly, these NK cells were functionally competent upon tumor interaction at this early time point.